Resource mobilization for tetanus vaccination in Vietnam: Uptake, demand and willingness to pay among women of reproductive age - Nguyen, Thang Huu; Le, Xuan Thi Thanh; Nguyen, Long Hoang; Le, Huong Thi; Do, Toan Thanh Thi; Nguyen, Huong Lan Thi; Nguyen, Hien Thu; Latkin, Carl A.; Ho, Cyrus S. H.; Ho, Roger C. M. (Frontiers in Public Health, 2022)
Introduction: Tetanus vaccine coverage in Vietnam has been declining in recent years due to rapid population growth rate, shrinking budget and inefficient resource mobilization strategy. This study examined the uptake, demand, and willingness to pay (WTP) for tetanus vaccines in Vietnamese women of reproductive age as well as determined associated factors and assessed feasibility of the long-term tetanus vaccine resource mobilization scheme. Methods: Cross-sectional data were obtained on 807 women of childbearing age in Hanoi, Vietnam in 2016. Tetanus vaccine uptake, demand and willingness to pay were collected by using a structured questionnaire. Multivariable logistic and interval regression models were used to examine associated factors with vaccine uptake, demand, and WTP. Results: Of 807 participants, 42.4% and 64.8% had sufficient tetanus vaccination (i.e. received at least three doses of vaccine) and were willing to pay for tetanus vaccination. The mean amount of WTP for one dose of tetanus was US$ 7.3 (95%CI=6.7-7.9). Having children or being aware that the tetanus vaccine was free-of-charge were negatively associated with WTP for tetanus vaccine. Having high school education, living in a rural area, and not being aware of vaccine price or being aware that vaccines were provided freely reduced the amount of WTP. WTP increased among women receiving information from friends and relatives. Discussion: This study indicated a low tetanus vaccination coverage and a moderate degree of WTP for tetanus vaccine among Vietnamese women of childbearing age. Target-specific educational and financial support interventions, along with efforts to reduce vaccination costs are critical to improving the vaccine uptake, demand, and WTP for tetanus immunization among women.